Antimicrobial and antioxidant potential of Yemeni Sidr honey against multidrug-resistant pathogens – in vitro and in silico studies - Hani A. Alhadrami; Ahmed M. Sayed; Hossam M. Hassan; Mostafa E. Rateb; Marwa A. Taher (Future Journal of Pharmaceutical Sciences)
Abstract Background Honey’s medical values have been extensively recorded in literature. Yemeni Sidr honey was reported to treat many ailments like stomach and respiratory disorders. ESKAPE and other multidrug-resistant pathogens are considered one of the top three risks to global public health, so alternative strategies become critical demand against such pathogens or their biofilms. The current study aimed to explore the antibacterial and antioxidant potential of the Yemeni Sidr honey extracts. The antibacterial activity of the two Yemeni Sidr honey extracts (ST and SM) was assessed against different pathogenic strains. The antioxidant activity was also evaluated using ORAC, ABST, 5-LOX, and DPPH. Furthermore, 2D HSQC data of both ST and SM honey extracts were collected uploaded to the SMART platform to identify the possible metabolites in these extracts. The identified metabolites were analyzed using docking and molecular dynamic simulations (MDS) to identify the key players in the antibacterial action. Results The antibacterial activity revealed that ST and SM extracts have similar activity against all tested pathogens. ST extract exhibited superior antibiofilm effect against P. aeruginosa and C. albicans by 68.2% and 62.6%, respectively, exceeding the reference standards. Moreover, ST extract displayed the highest antioxidant power against all assays except the DPPH assay. SMART dereplication of the HSQC data of ST extract revealed the annotations of five carbohydrates (fructose, glucose, mannose, maltose, and sucrose); while, SM extract showed three major phenolic compounds (chrysin, ellagic acid, and caffeic acid), in which chrysin and ellagic acid were likely the key players in the antibacterial action, based on MDS. Conclusions The study confirmed the effectiveness of Sidr honey against the tested multidrug-resistant pathogens. Additionally, our observations shed the light on the main secondary constituents in Yemini Sidr honey extracts, and their effective role in multidrug-resistant pathogens growth inhibition.